Does Economic Policy Uncertainty Affect the Composite Stock Price Index? Evidence from Seven Asian Countries - Rizki Febri Pratama; Istiqomah (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2026)
Economic Policy Uncertainty (EPU) is one of the crucial factors affecting investors' decisions to invest in global capital markets. This study aims to analyze the movement of the Composite Stock Price Index (CSPI) due to the influence of EPU, covering seven Asian countries, including Hong Kong, Japan, Pakistan, China, India, South Korea, and Singapore. The data used is monthly panel data from January 2010 to January 2025, employing the Feasible Generalized Least Squares (FGLS) method based on Cross-Section SUR (PCSE). The primary independent variable studied is EPU, with control variables including interest rates, inflation, and exchange rates. The analysis shows that EPU has a significant positive effect on the CSPI, indicating that an increase in global EPU can trigger a shift in investment to developing countries and sectors that are safe or resistant to uncertainty shocks. Meanwhile, interest rates and inflation indicate a significant negative impact on the CSPI, consistent with the theory that stock market performance is negatively affected by rising capital costs and declining purchasing power. Conversely, the exchange rate shows a significant positive impact on the CSPI, where the appreciation of the domestic currency increases investor confidence and improves export competitiveness. This study emphasizes the urgency of stabilizing the aggregate economy and managing perceptions in the face of economic policy uncertainty as a tactic to maintain investor interest in the stock market, thereby promoting sustainable economic development through long-term investments.